Transition temperature in KDP type crystals under external pressures. Role of H-bond geometry - Levitskii, R.R.; Moina, A.P.; Zachek, I.R. (Condensed Matter Physics, 1999)
Within the four-particle cluster approximation for the proton ordering model,
we study effects of external pressures which do not lower the symmetry
of crystals on deuterated ferroelectrics and antiferroelectrics of KH₂PO₄
family. We show that the universality of the transition temperature vs D-
site distance dependence observed experimentally in some of the crystals
deformed by hydrostatic pressure is also obeyed by the other crystals of
the family as well as under the uniaxial pressure p = −σ₃. У наближенні чотиричастинкового кластера для моделі протонного
впорядкування досліджуються ефекти, викликані зовнішніми тисками, що не понижують симетрії кристалів, на дейтеровані сегнетоелектрики і антисегнетоелектрики сім’ї KH₂PO₄. Показано, що експериментально виявлена для деяких з цих кристалів, деформованих
гідростатичним тиском, універсальна залежність температур переходу від віддалі між можливими положеннями дейтрона на зв’язку,
поширюється також і на інші кристали цієї сім’ї, що можуть бути деформовані і одновісним тиском.